A CRITICAL DESIGN-SURPASSING: ANALYSIS OF THE CHARACTERISTICS AND METHODS OF TEACHING PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
This article was based on a bibliographical study, using as sources of study, books, scientific articles, graduate theses, among others. The present study has the objective to analyze and identify some characteristics that involve the design of Physical Education called Critical-surpassing, such as their training base; scholars who defend it; principles that guide their way of understanding the Physical Education school. With an action exploratory study claim to understand how it performs the methodological process of teaching and learning in view of the proponents of this approach. In studies undertaken it is clear that, according to the conception analyzed, Physical Education adopts the object of his practice, body culture, understood as ways of representing the world that man has produced in the course of history and exteriorized through bodily expression; also seeks to understand how this knowledge develops vision Crit-surpassing, relating to goals, teaching principles and evaluation, among others guiding conception. It states that one of the conclusions of this paper is that the design of the study in Physical Education strive for maturation of critical thinking helps in the formation of a society with citizens more critical, autonomous and aware, so builders social reality.
Keywords: Physical Education; Crit-surpassing design; Body culture.